PELATIHAN PENGEMBANGAN SOAL BERBASIS HOTS BAGI GURU SMP NEGERI 1 WIRADESA PEKALONGAN - Sayyidatul Karimah; Rini Utami (Universitas PGRI Yogyakarta, 2022)
Learning assessment is expected to assist students in improving higher order thinking skills (HOTS). In accordance with these conditions, teachers are also required to be able to develop HOTS-based questions as an assessment instrument. This training activity aims to provide training and assistance to teachers of SMP Negeri 1 Wiradesa regarding the development of HOTS-based questions consisting of the concept of HOTS questions, the characteristics of HOTS questions, and how to develop them. The methods used in this training include planning, implementing and evaluating training. The training participants amounted to 46 teachers who were teachers of SMP Negeri 1 Wiradesa. The results of this training activity are teachers can find out how to develop HOTS-based questions and can practice them according to the subjects taught. keyword: Development, Questions, HOTS